Methods for Analysing and Reporting EQ-5D Data - Devlin, Nancy (Springer Nature, 2020)
This open access book is the first published guide about how to analyse data produced by the EQ-5D, one of the most widely used Patient Reported Outcomes questionnaires world wide. The authors provide practical, clear and comprehensive guidance in five concise chapters. Following an overview of the EQ-5D and its analysis, we describe how the questionnaire data - the EQ-5D profile and EQ VAS - can be analysed in different ways to generate important insights into peoples' health. We then show how the value sets which accompany the EQ-5D can be applied to summarise patients' data. The final chapter deals with advanced topics, including the use of Minimally Important Differences, case-mix adjustment, mapping, and more. This book is essential for those new to analyzing EQ-5D data and will be also be valuable for those with more experience. The methods can be applied to any EQ-5D instrument (for example, the three- and five-level and Youth versions) and many of the methods described will be equally relevant to other Patient Reported Outcomes instruments. ; This book provides the first guidance for users of the EQ-5D, a widely used measure of patient reported health around the world, on how to analyse data Provides detailed and comprehensive guidance on methods for analysing and reporting EQ-5D data The book is accompanied by code, in R, SPSS, STATA and SAS to allow users to implement the methods on their own data The book is accompanied by a slide deck, for use by instructors wishing to teach the methods